The Concept of "Elective Likeness" in the Sociology of the Juridical Culture (Revista da Faculdade de Direito, Universidade de São Paulo, 1997)
Natural Sciences' terminology has been still used frequently to elaborate the sociological concepts on account of Contism. Nevertheless the fundamental ideas of social sciences must be framed into words capable of describing satisfactorily the flowing sociocultural phenomena. The alchemical expression "elective affinity", for example, has been turned into a sociological concept in order to explain the non-mechanical alliances between sociocultural systems. It can be also useful to Sociology of Juridical Culture for making clear some relations between comprehensive systems about Law and some political, economical and religious tendencies.